2016
DOI: 10.1186/s13068-016-0458-5
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting of freshwater microalgae with microbial bioflocculant: a pilot-scale study

Abstract: BackgroundNowadays, bioflocculation is considered as a potential technology that could be able to alleviate microalgae dewatering cost regarded as the cornerstone hindrance of their full-scale application. However, most bioflocculation studies reported are laboratory scales. This study examined a pilot-scale and in situ flocculation of freshwater microalgae Desmodesmus brasiliensis by microbial bioflocculant. Biochemical composition of microalgal biomass was analyzed to evaluate the applicability of biofloccul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Owing to the serious threats caused by metal accumulation in food chain, metal-ions based flocculation can not be considered as a safe and eco-friendly technology. Recently, some studies reported the coagulation effects of natural polymers, such as protein and polysaccharide, secreted by microorganisms [78,79]. Generally, by natural-polymer based flocculation, the harvesting efficiency of microalgae could reach 90% [78,80].…”
Section: Flotation and Modified Flotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the serious threats caused by metal accumulation in food chain, metal-ions based flocculation can not be considered as a safe and eco-friendly technology. Recently, some studies reported the coagulation effects of natural polymers, such as protein and polysaccharide, secreted by microorganisms [78,79]. Generally, by natural-polymer based flocculation, the harvesting efficiency of microalgae could reach 90% [78,80].…”
Section: Flotation and Modified Flotationmentioning
confidence: 99%
“…Recently, some studies reported the coagulation effects of natural polymers, such as protein and polysaccharide, secreted by microorganisms [78,79]. Generally, by natural-polymer based flocculation, the harvesting efficiency of microalgae could reach 90% [78,80]. Therefore, it is suggested that in aquaculture, to harvest microalgae by flotation-flocculation, natural polymers can be used for safety purpose.…”
Section: Flotation and Modified Flotationmentioning
confidence: 99%
“…Wang et al isolated a novel bacterium HW001 from Permian groundwater and demonstrated that this strain is able to stimulate aggregation of both Nannochloropsis oceanica IMET1 and other potential biofuel-producing green microalgae, diatoms and cyanobacteria (Wang et al, 2012a). In addition, two potent bioflocculants have been discovered from culture supernatant of Burkholderia cepacia (Manheim and Nelson, 2013) and Bacillus licheniformis CGMCC 2876 (Ndikubwimana et al, 2016). High flocculation efficiency of Desmodesmus brasiliensis (> 98 %) was achieved at pilot-scale treatment with poly-c-glutamic acid, a bioflocculant produced by Bacillus licheniformis CGMCC 2876 (Manheim and Nelson, 2013).…”
Section: Downstream Processing Of Algal Biomass Using Symbiontsmentioning
confidence: 99%
“…New low-cost harvesting technology is required to make the whole process sustainable since harvesting is considered as a major challenge as it is requiring almost 30% of the total cost of the pharmaceuticals production process. Different initiatives are recently developed but still they didn't meet the viability [109][110][111][112]. Furthermore, the extraction process that is efficient, safe for the molecules, economically feasible and environmentally friendly is far from being a reality.…”
Section: Economic Feasibility and Challenges In Using Microalgae For mentioning
confidence: 99%